2020
DOI: 10.2147/cmar.s269768
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gambogic Acid Inhibits the Progression of Gastric Cancer via circRNA_ASAP2/miR-33a-5p/CDK7 Axis</p>

Abstract: Background: Gastric cancer (GC) is a major cancer-related mortality disease. Gambogic acid (GA) has been investigated to inhibit cancer progression. In the present study, the molecular mechanism of GA in regulating GC progression was studied. Methods: The expression levels of circular RNA ASAP2 (circ_ASAP2), miR-33a-5p and cyclin-dependent kinases 7 (CDK7) were detected by quantitative real-time polymerase reaction (qRT-PCR). CDK7 protein level was evaluated by Western blot. Cell colony formation assay, 3-(4,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…110 This review summarizes the mechanism of circRNAs involved in tumor cell cycle regulation and finds that their abnormal expression in tumors not only plays a role in tumor proliferation but also in tumor invasion and metastasis, TNM staging, histological grade, malignant phenotype, sensitivity to chemotherapy drugs and patient survival. 3,5,8,9,[25][26][27][28][29][30][31][32][33][111][112][113][114] These findings highlight potential biomarkers for tumor diagnosis and provide an effective reference for developing future tumor treatments involving the regulation of the cell cycle based on circRNA.…”
Section: Discussionmentioning
confidence: 86%
“…110 This review summarizes the mechanism of circRNAs involved in tumor cell cycle regulation and finds that their abnormal expression in tumors not only plays a role in tumor proliferation but also in tumor invasion and metastasis, TNM staging, histological grade, malignant phenotype, sensitivity to chemotherapy drugs and patient survival. 3,5,8,9,[25][26][27][28][29][30][31][32][33][111][112][113][114] These findings highlight potential biomarkers for tumor diagnosis and provide an effective reference for developing future tumor treatments involving the regulation of the cell cycle based on circRNA.…”
Section: Discussionmentioning
confidence: 86%
“…3 a. As a previous study has indicated that circRNA_ASAP2 (has_circ_0006089) was associated with the progression of GC [ 26 ], further experiments were conducted to investigate the involvement of circRNA_ASAP2 in As4S4-modulated biological behavior alterations in GC cells. Moreover, the expression of circRNA_ASAP2 was significantly decreased in GC cells treated with 1 and 2 μM As 4 S 4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the proliferation, migration and invasion were significantly promoted in GC cells after the transfection with pc-circRNA_ASAP2, but these effects were abolished by As 4 S 4 treatment. Similarly, a recent study has also revealed the involvement of circRNA_ASAP2 in the regulation of tumor growth and metastasis in GC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Dan Lin et al and Qiong Wu et al explored that the expression of miR-33a-5p was descending in GC. However, how it regulates drug resistance of target genes was rarely studied [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%